Knowledge and Preventive Practices on Community-Acquired Pneumonia Among Residents in General Santos City - Dajay, Jules Alexis (Journal of Interdisciplinary Perspectives, 2024)
This descriptive-correlational study described the profile of respondents and determined the association between knowledge and preventive practices regarding Community-Acquired Pneumonia (CAP) among residents in ten selected barangays in General Santos City. A validated self-made pen-and-paper test and survey questionnaire were used to determine the demographic profile, knowledge, and preventive practices on CAP among 300 respondents selected through quota sampling. The study revealed that most respondents were aged 41-50 years old, female, married, had an extended family structure, had reached the high school level, had an estimated monthly income of less than P 10,000.00, and had no family history of CAP. It was found that most respondents had very low knowledge about the diagnosis of the disease and a very low perception of rest/sleep and physical activity as significant preventive practices for CAP. A significant relationship between knowledge and preventive practices on CAP was identified. Therefore, it is necessary to intensify information, education, and communication (IEC) campaigns to improve awareness of CAP. The study suggests partnerships between public and private organizations to initiate, facilitate, and coordinate programs aimed at reducing CAP and providing training for the implementers of IEC campaigns. Additionally, a high level of healthy practices should be maintained and strengthened through various program interventions by allocating funds at city and barangay levels. Further research is recommended to determine the effects of demographic profiles on the knowledge and preventive practices of CAP.